PRINCIPLES OF SELF-IMPROVEMENT OF A VOCATIONAL COLLEGE TEACHER: PERSONAL ASPECT (Innovative professional education, 2024)
The subsection substantiates the professional and pedagogical self-development of a teacher as a creative process that ensures the growth of professionalism and pedagogical skills of a specialist; as a scientific phenomenon that determines the need for self-movement of a teacher, rejection of conservatism and reproductiveness in favour of the development of his/her own pedagogical creativity
Keywords: principles, vocational college teacher, self-improvement, creative process, personal qualities, scientific phenomenon